First-generation merozoites of caprine Eimeria christenseni are capable to invade and egress primary host endothelial cells in vitro - Silva, L.M.R.; Ruiz, A.; Barba, E.; Lopéz-Osorio, S.; Molina, J.A.; Molina, J.M.; Taubert, A.; Hermosilla, C. (Frontiers in Veterinary Science, 2025)
The caprine Eimeria christenseni species belongs to the phylogenetic clade of pathogenic ruminant Eimeria, replicating within the endothelial cells of central lymph capillaries of the ileum villi in vivo. Investigations on E. christenseni-host endothelial cell interactions, including cell invasion, egress, apoptosis, senescence, cell cycle, cytoskeleton, cell metabolism and endothelium-derived innate immune reactions are possible to achieve through permissive in vitro culture systems. Therefore, we here established a suitable in vitro E. christenseni (strain GC) culture system using primary bovine umbilical vein endothelial cells (BUVEC) for the development of first-generation macromeronts. After 18–22 days post infection (p.i.), the intracellular sporozoites matured into fully developed E. christenseni-macromeronts, releasing viable merozoites I. Interestingly, two different types of E. christenseni-merozoites I were observed, i.e., thinner and thicker merozoites I. The thinner ones were more active, presented typical gliding motility, and were found intracellularly shortly after their release, while the thicker ones were less active and invasive to BUVEC. Thinner E. christenseni merozoites I actively invaded and egressed host cells by breaching the plasma membrane without host cell lysis, a phenomenon exclusively reported so far for apicomplexan sporozoites of Plasmodium yoelii and Eimeria bovis. Additionally, intracellular E. christenseni merozoites I were monitored over time (up to 30 days), thereby revealing no further development into meront II stages. Further research is needed to assess whether primary endothelial cells of caprine origin could support the complete life cycle of E. christenseni in vitro. This novel in vitro system will contribute not only for further studies on Eimeria-derived invasion- and egress strategies, endothelial cell-derived innate immune reactions, but also for merozoites I- and antigen production requested for vaccination strategies as already reported for other ruminant Eimeria species.